Keadilan Organisasi Dan Iklim Organisasi Serta Pengaruhnya Terhadap Keinginan Keluar (Intention To Quit) Dengan Komitmen Organisasional - Ester Praja Anggriany Pangabean (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2021)
The purpose of this study is to find out how much influence organizational justice and organizational climate have on the intention to quit partially. To find out how much influence the moderation of organizational commitment can strengthen organizational justice and organizational climate Agathe inst intention to quit the North Sumatra Provincial Parliament Secretariat Office. The population in this study were contract employees of the Secretariat Office of North Sumatra Province, amounting to 103 people. The sample in this study were contract employees at the Secretariat of the North Sumatra Province DPRD, as many as 103 people using population research techniques. Data analysis techniques used are multiple linear regression and MRA. The results showed that the organizational justice variable significantly affected the intention to quit. Organizational climate variables do not significantly inflate the intention to quit. Organizational commitment has the effect of strengthening the effect of organizational jujustice on intention to quit. Organizational commitment has the effect of strengthening the influence of organizational climate the on intention to quit.